Intralesional Marginal Resection for Osteoblastoma in the Mobile Spine: Experience From a Single Center - Cao, Shiliang; Chen, Keyuan; Jiang, Liang; Wei, Feng; Liu, Xiaoguang; Liu, Zhongjun (Frontiers in Surgery, 2022)
Osteoblastoma (OB) is a benign bone tumor with aggressive behavior and a tendency for local recurrence. The appropriate surgical strategy for spinal OB remains unclear. This retrospective study aimed to verify the clinical efficacy and safety of intralesional marginal resection of OB in the mobile spine. We enrolled 50 consecutive patients with spinal OB between January 2009 and December 2019. The tumors were staged based on the Enneking system, with 21 and 29 lesions being determined as stage 2 (St.2) and stage 3 (St.3), respectively. Among them, 42 patients underwent intralesional marginal resection, five underwent extensive curettage, and three underwent en bloc resection successfully since their lesions were limited to the posterior element in a single vertebra. We analyzed clinical characteristics, perioperative and follow-up images, surgical details, and follow-up data. Within a median follow-up duration of 50 (range: 24–160) months, six (12.0%) patients had local recurrence. The recurrence rates among patients who underwent intralesional marginal resection, curettage, en bloc resection were 7.1% (3/42), 60.0% (3/5), and 0% (0/3), respectively. The recurrence rate of intralesional marginal resection of St.3 lesions was slightly higher than that of St.2 lesions (7.7% [2/26] vs. 6.3% [1/16]). There were 16 (38.1%), 3 (60.0%), and 0 patients with surgical complications among those who underwent intralesional marginal resection, curettage, and en bloc resection, respectively. Local recurrence was observed in five (5/14, 35.7%) patients who had vertebral artery extension and in no patients who did not have vertebral artery extension (p = 0.02). Our findings suggest that intralesional marginal resection could be an appropriate treatment choice for patients with spinal OB, both St.2 and St.3 lesions, with an acceptable local recurrence rate and a low risk of complications. Vertebral artery extension could be a strong risk factor for local recurrence in patients with spinal OB.